Lysis of myotubes by alloreactive cytotoxic T cells and natural killer cells. Relevance to myoblast transplantation. - Hohlfeld, R (1990)
The aim of this study was to investigate the susceptibility of human myotubes to lysis by the two major types of cytotoxic effector cells, CD3+CD8+ cytotoxic T cells (CTL) and CD16+CD56+ natural killer (NK) cells. The myoblasts preparations used as target cells were greater than 90% pure as assessed by immunostaining with the Leu19 monoclonal antibody (MAb) that cross-reacts with the neural cell adhesion molecule N-CAM. Allospecific CTL lines were generated from mixed lymphocyte cultures, and freshly isolated allogeneic and autologous peripheral blood cells were used as a source of NK cells. The cytotoxicity was observed under phase optics and by immunoelectron microscopy, and was quantitated with a chromium release assay. Myotubes were efficiently killed by allospecific CTL and by autologous and allogeneic NK cells. The killing by CTL was inhibited with an anti-class I HLA MAb, and the killing by NK cells was inhibited by depleting peripheral blood cells of CD16+ cells with anti-CD16 MAb and complement. The results have important implications for myoblast transplantation, an experimental therapy of muscular dystrophy.